Increased reward value of non-social stimuli in children and adolescents with autism - Watson, Karli K.; Miller, Stephanie; Hannah, Eleanor; Kovac, Megan; Damiano, Cara R.; Sabatino-DiCrisco, Antoinette; Turner-Brown, Lauren; Sasson, Noah J.; Platt, Michael L.; Dichter, Gabriel S. (Frontiers in Psychology, 2015)
We used an econometric choice task to estimate the implicit reward value of social and nonsocial stimuli related to restricted interests in children and adolescents with (n=12) and without (n=22) ASD. Mixed effects logistic regression analyses revealed that children and adolescents with ASD were willing to receive less cash payout to view restricted interest stimuli, whereas children and adolescents without ASD were indifferent to cash payouts to view these images. Groups did not differ in valuation of social images or nonsocial images unrelated to restricted interests. Our findings reveal that individuals with ASD assign enhanced reward value of nonsocial stimuli related to restricted interests in ASD. These results suggest that motivational accounts of ASD should also consider the reward value of restricted interests in addition to that of social stimuli (Dichter & Adolphs, 2012).